2019
DOI: 10.1039/c9ra05419g
|View full text |Cite
|
Sign up to set email alerts
|

Planar graphitic ZnS, buckling ZnS monolayers and rolled-up nanotubes as nonlinear optical materials: first-principles simulation

Abstract: Contradictory large SHG coefficients and wide bandgaps are simultaneously discovered in planar graphitic ZnS, buckling ZnS monolayers and rolled-up nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…Optimized silicene shows buckled structure with a buckling height of 0.46 Å while optimized ZnS monolayer shows a planar graphene-like structure. These values are in good agreement with earlier studies [33,34]. Since the lattice mismatch for these two monolayers is 0.77% only, the heterostructure can be expected to form without difficulty.…”
Section: Structural Arrangement and Stabilitysupporting
confidence: 92%
“…Optimized silicene shows buckled structure with a buckling height of 0.46 Å while optimized ZnS monolayer shows a planar graphene-like structure. These values are in good agreement with earlier studies [33,34]. Since the lattice mismatch for these two monolayers is 0.77% only, the heterostructure can be expected to form without difficulty.…”
Section: Structural Arrangement and Stabilitysupporting
confidence: 92%
“…From the calculated conduction band and valence band (VB) values (Table 2), the VB values shifted to higher values (0.4459 eV) for ZnS-ZnO-rEPS. The values reported in Table 2, and the results from the simulations showed that the ZnO-ZnS sample exhibited a direct band gap similar to the reported results in previous studies [22,23]. The ZnS-ZnO-rEPS sample, shows an indirect band gap and the calculated band gap value for the nanocomposite of rEPS with ZnO and ZnS has not been reported elsewhere.…”
Section: Band Structuresupporting
confidence: 88%
“…The theoretical explanation of the resonant effect on SHG was studied by Hu et. al., which can be reflected by the dielectric function of the linear optical process. When materials are irradiated by a powerful laser, the second-order nonlinear polarizability can be written as a coupling of the laser electric field component and the second-order nonlinear coefficient susceptibility as follows P i ( λ 2 , θ , α , ϕ ) j , k χ italicijk × false( ϕ false) E j false( λ , θ , α false) E k false( λ , θ , α false) where χ ijk is the second-order nonlinear optical susceptibility, which is a third-rank tensor, ε 0 is the permittivity of vacuum, λ is the wavelength, and θ, α, and ϕ are the incident, polarized, and azimuthal angles, respectively.…”
Section: Resultsmentioning
confidence: 99%